Religion and Party Choice in Europe - Hobolt, S; van der Brug, W; de Vreese, C (2009)
This paper investigates religiosity in relation to party choice in European Parliament elections. Conventional wisdom tells us that as Europe has secularised, the effect of religion on party choice should also have diminished. Yet, this cross-national and cross-temporal study of religious voting in European elections from 1989 to 2004 paints a more nuanced picture. It shows that a) the effect of religion has been declining, but has increased in recent years, b) religion matters in particular for voting for Christian Democratic parties and Conservative parties, c) while generational replacement reduces the overall effect of religion on electoral decisions, the effect of religion has recently increased within each generation, and d) the impact of religion depends on the religious context in which citizens live so that religion plays a bigger role in fractionalised societies. These findings are discussed in the light of a revived importance of religion for European politics.